The syntax and grammar of journalistic text to attract the audience’s attention - Alina Damirovna Nazmieva, Svetlana Yurievna Glushkova, Tkhompira Chitra, (Opción, 2019)
The article deals with features of the syntax and grammar of the journalistic text, as a way to attract the attention of the audience via comparative qualitative research methods. As a result, the overall goal of a journalistic style is to influence public opinion, convince the reader or listener that the interpretation given by the author or speaker is the only correct one, and force him to accept the point of view expressed in speech, essay or article. In conclusion, studying any foreign language as a means of communication should go in hand with learning the journalistic text.